Kelayakan Media Pembelajaran Biorgam Untuk Meningkatkan Pemahaman Materi Organ Tubuh Manusia Di Kelas V Madrasah Ibtidaiyah - Risda Lailul Yulfa Fitria; Sunanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education in simple terms is a learning process carried out in schools, one of which is learning Natural Sciences or Natural Sciences, in the learning process it requires learning media to achieve learning objectives and solutions to problems such as students' lack of interest, lack of motivation to learn, a presumption that learning is difficult, and the media used is irrelevant. This study discusses the development of biogam learning media on Human Organs in grade V elementary school. The aim of the research was to develop biogam media in science learning on Human Organs in grade V as a solution to problems, find out the feasibility of biogam media, and produce biogam learning media. This type of research uses development research with the research model used is the 4-D model. This model consists of Define, Design, Develop, and Disseminate. The limitation of doing research is that the research is carried out until the Develop stage only, namely into 3-D. The object in the research is bioorganism learning media. The media developed in the study were validated by 2 validators. The results of the two validators on biogam learning media produce a calculation of 97.414% with a very valid category and suitable for use in elementary schools.